NSW Government response to the Legislative Council General Purpose Standing Committee No. 2 inquiry into complaints handling within NSW Health - New South Wales; New South Wales. Department of Health; NSW Health (North Sydney, N.S.W. : NSW Dept. of Health, 2005)
"The NSW Government welcomes the Committee's report and its contribution to improving complaints handling processes in NSW Health. Open and thorough discussion of issues is important, and a key step in improving the quality of the systems through which we deliver services to the community. This Government is seeking to develop a health system where health practioners proactively and openly provide patients and their families with timely and frank information when an adverse event has occurred."--P. 1.
Cover title.
"March 2005"--Inside front cover.
Bibliography: p. 17.
Keywords: New South Wales. -- Parliament. -- Legislative Council. -- General Purpose Standing Committee No. 2.; Complaints (Administrative procedure) -- New South Wales; Communication in medicine -- New South Wales; Health facilities -- Complaints against -- New South Wales; Medical care -- New South Wales -- Quality control